2003
DOI: 10.1074/jbc.m304816200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Kinase Mediates Cytokine- and Calcium Ionophore-induced Arachidonic Acid Release

Abstract: Despite the importance of prostaglandins, little is known about the regulation of prostanoid synthesis proximal to the activation of cytosolic phospholipase A 2 , the initial rate-limiting step. In this study, ceramide-1-phosphate (C-1-P) was shown to be a specific and potent inducer of arachidonic acid (AA) and prostanoid synthesis in cells. This study also demonstrates that two well established activators of AA release and prostanoid synthesis, the cytokine, interleukin-1␤ (IL-1␤), and the calcium ionophore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
207
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(216 citation statements)
references
References 44 publications
6
207
0
3
Order By: Relevance
“…This suggests that Cer-1-P does not solely promote association of the enzyme with membranes. Our data fully support a formerly proposed mechanism (32,40) whereby Cer-1-P activates the JNK cascade, either directly or after the inhibition of protein phosphatases 1 and 2A. This mechanism is in keeping with our observation that okadaic acid induces LD biogenesis in a JNK-and cPLA 2 ␣-dependent fashion.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that Cer-1-P does not solely promote association of the enzyme with membranes. Our data fully support a formerly proposed mechanism (32,40) whereby Cer-1-P activates the JNK cascade, either directly or after the inhibition of protein phosphatases 1 and 2A. This mechanism is in keeping with our observation that okadaic acid induces LD biogenesis in a JNK-and cPLA 2 ␣-dependent fashion.…”
Section: Discussionsupporting
confidence: 80%
“…However, recent studies by Chalfant's group suggested that C1P is the actual regulator of AA and prostaglandin (PG) production (Pettus et al, 2003). The importance of CERK, and its product C1P, in cell signaling was highlighted by using specific siRNA to down-regulate its activity in A549 lung adenocarcinoma cells.…”
Section: C1p Regulates Inflammationmentioning
confidence: 99%
“…This treatment inhibited AA release and PGE 2 production in response to a calcium ionophore and to interleukin 1 (IL-1 (Chalfant and Spiegel, 2005;Pettus et al, 2003). Of relevance, C1P was shown to be generated by the actions of either a calcium ionophore or IL-1 on A549 lung adenocarcinoma cells (Pettus et al, 2003), and M-CSF on bone A c c e p t e d M a n u s c r i p t 4 marrow-derived macrophages (BMDM) (Gangoiti et al, 2008b). A crucial discovery was the direct implication of C1P in the inflammatory response.…”
Section: C1p Regulates Inflammationmentioning
confidence: 99%
“…In these experiments, an aqueous dispersion of C1P was prepared by sonication, and the optimal concentration of C1P was 30 lM. When C1P is dissolved in a mixture of 49:1 methanol/dodecane or ethanol/ dodecane, dispersion is improved and effects on cell proliferation in fibroblasts or arachidonic acid release in A549 cells have been reported at concentrations as low as 2.5 lM [3,6,7]. In the present work, we found that although 2.5 lM C1P was effective in promoting macrophage survival when added in methanol/dodecane, the solvent mixture alone caused an increase of about 18% on macrophage survival, and therefore it was decided not to use methanol/ dodecane in subsequent experiments.…”
Section: C1p Stimulates the Pi3-k/pkb Pathwaymentioning
confidence: 99%
“…Ceramide-1-phosphate (C1P) is emerging as a new bioactive molecule [1] capable of regulating vital pathophysiological functions including cell proliferation [2,3], apoptosis [4], phagocytosis [5], and inflammation [6,7]. Although the existence of C1P and its metabolizing enzymes, ceramide kinase and C1P phosphatase, in mammalian tissues have been known for over a decade [8][9][10], current understanding of the metabolic and signaling pathways that are affected by this bioactive sphingolipid is incomplete.…”
Section: Introductionmentioning
confidence: 99%